Five on a secret trail - Blyton, Enid; Soper, Eileen Alice (Hodder Children's London, 1997)
"The Famous Five are camping near an old ruined cottage - but is the cottage really abandoned? Anne hears strange noises at night, but the others don't believe her! Then they see ghostly lights ."--B.cover